Entre o "instinto" e a "falta de hábito": a psiquiatrização da sexualidade em Bom-Crioulo (1895) - Lara Neto, Oswaldo Alves (2009)
A productive dialogue marked the interaction among novelists and scientists adepts from deterministic theories in the late 19th century. We start with the contextualization of this fundamental period to history of sexuality in modern societies to realize analytical reading of Adolfo Caminha s novel, Bom-Crioulo (1895). The projects that based discourses in this period answered to the question of homoerotism like social and medical matter. In this work, we discuss like this biopolitical reading in Brazilian society was elaborated in Caminha s novel and from the jurist Francisco Viveiros de Castro, defining it in accordance with Brazilian racism.